TiO2-pattern-modulated actuation of an agarose@CNT/agarose bilayer induced by light and humidity. Issue 18 (25th April 2018) - Tu, Yaqing; Yuan, Jun; Lei, Dan; Tan, Huiyan; Wei, Jiang; Huang, Wei; Zhang, Lidong
Abstract : A smart bilayer of AG@CNT/AG composed of carbon nanotubes (CNTs) and agarose (AG) is developed. Abstract : A smart bilayer of AG@CNT/AG composed of carbon nanotubes (CNTs) and agarose (AG) is developed. TiO2 patterns which partly reflect light are introduced at the bilayer surface, giving rise to a spatially selective photothermal effect that can be used to induce shape-programmed motility upon light irradiation. The TiO2 patterns also result in the bilayer with a differential flexural modulus and can thus modulate its motility induced by humidity.